Selective Pharmacological Modulation of Pyramidal Neurons and Interneurons in the CA1 Region of the Rat Hippocampus - Martina, Marzia; Comas, Tanya; Mealing, Geoff A. (Frontiers in Pharmacology, 2013)
The hippocampus is a complex network tightly regulated by interactions between excitatory and inhibitory neurons. In neurodegenerative disorders where cognitive functions such as learning and memory are impaired this excitation-inhibition balance may be altered. Interestingly, the uncompetitive NMDAR antagonist memantine, currently in clinical use for the treatment of Alzheimer’s disease (AD), may alter the excitation-inhibition balance in the hippocampus. However, the specific mechanism by which memantine exerts this action is not clear. To better elucidate the effect of memantine on hippocampal circuitry, we studied its pharmacology on NMDAR currents in both pyramidal cells (PCs) and interneurons (Ints) in the CA1 region of the hippocampus. Applying whole-cell patch-clamp methodology to acute rat hippocampal slices, we report that memantine antagonism is more robust in PCs than in Ints. Using specific NMDAR subunit antagonists, we determined that this selective antagonism of memantine is attributable to specific differences in the molecular make up of the NMDARs in excitatory and inhibitory neurons. These findings offer new insight into the mechanism of action and therapeutic potential of NMDA receptor pharmacology in modulating hippocampal excitability.